Analisis Kinerja Keuangan Perusahaan dengan Menggunakan Pendekatan Economic Value Added (EVA) dan Market Value Added (MVA) pada Perusahaan Farmasi yang Go Public di Bursa Efek Indonesia Tahun 2008-2011 - Eskasari, Weny Mey; dro, Harlen (Jurnal Ilmiah Mahasiswa FEB, 2012)
Better economic growth gives opportunity for business people to increase their profits. At the other side, it is also increase tight rivalry between businesses.  Good performance  management  is needed  in order  to  achieve  the company's goals  and to maximalize investor’s prosperity. This study uses descriptive quantitative method, which aims to determine the  company's financial performance  using  analysis tools  Economic Value Added  (EVA)  and Market  Value Added  (MVA)  in  pharmaceutical  companies,  namely  PT. Darya Varia Laboratories Tbk, PT. Kalbe Farma Tbk, PT. Merck Tbk, PT. Pyridam Farma Tbk,  and  PT.  Tempo  Scan  Pacific  Tbk.  The data used  in this study  is a  secondary data obtained from Pojok BEI Faculty of Economics and Business Universitas Brawijaya Malang. The result shows that during the four (4) years of the study, five pharmaceutical companies are producing positive EVA value. It means that management has succeeded in creating added value for its investors because it met the investors’s expectations to earn returns over the issuance of capital. While the MVA value shows diverse results. Positive result of MVA indicates that the management has been able to increase the wealth of its investors, while a negative value indicates that the MVA management has demolished the wealth of its investors. Keywords :  Financial Performance, Economic Value Added  (EVA), Market Value Added (MVA)